On the sensitivity of the evaporative pattern deposition of particulate mass to the ionic strength in kinetically stable suspensions - Zigelman, Anna; Homede, Ekhlas; Manor, Ofer (The European physical journal. ST, Special topics, 2020)
The deposition of particulate mass from a volatile suspension is a common process. Usually, the employed suspensions are designed to be kinetically stable, which is achieved by employing surface forces of molecular origin, e.g., the electrical double layer (EDL) or steric forces, to render high energy barriers to particle attachments. One may expect that a high energy barrier in the original suspension will render the deposit morphology solely connected to particle convection in the volatile liquid and, once most of the carrier liquid has evaporated, to capillary attraction between detached particles to each other and to the solid substrate. However, we show that variations in the magnitude of large energy barriers to particle attachments in our original suspensions are connected to variations in the deposit morphology following the evaporation of the carrier liquid. In our experiments, the different original EDL induced energy barriers are large and traverse tens and hundreds of K B T in magnitude. Nevertheless, the evaporation of the carrier liquid during the deposition process supports the convection of mass toward the three phase contact line between the suspension, substrate, and vapor phases. The convection of particle and ion mass dynamically increases particle concentration and ionic strength in the vicinity of the contact line. The elevated ionic strength reduces the energy barriers to particle attachments in that vicinity, which appears to locally support particle coagulation and adsorption effects and hence to alter the deposit morphology. Thus, the morphology of the deposit may show considerable sensitivity to the specific magnitude of energy barrier to particle attachments in the original, kinetically stable, suspension.